2000
DOI: 10.1046/j.1365-2826.2000.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Oreochromis mossambicus (tilapia) Corticotropin‐Releasing Hormone: cDNA Sequence and Bioactivity

Abstract: Although hypothalamic corticotropin-releasing hormone (CRH) is involved in the stress response in all vertebrate groups, only a limited number of studies on this neuroendocrine peptide deals with non-mammalian neuroendocrine systems. We determined the cDNA sequence of the CRH precursor of the teleost Oreochromis mossambicus (tilapia) and studied the biological potency of the CRH peptide in a homologous teleost bioassay. Polymerase chain reaction (PCR) with degenerate and specific primers yielded fragments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…However, in this area of research, only limited efforts have been made to study teleosts (12)(13)(14)(15)(16)(17). In this study, we identified a novel, teleost-specific member of the CRH family of neuropeptides, which we designated teleocortin (Tcn).…”
mentioning
confidence: 99%
“…However, in this area of research, only limited efforts have been made to study teleosts (12)(13)(14)(15)(16)(17). In this study, we identified a novel, teleost-specific member of the CRH family of neuropeptides, which we designated teleocortin (Tcn).…”
mentioning
confidence: 99%
“…In amphibians, TRH stimulates pituitary TSH release moderately in adult frogs but not in tadpoles, and it also induces PRL and GH secretion effectively (10,(21)(22)(23). Interestingly, CRH, a well-known ACTH-releasing factor in mammals (24,25), has been demonstrated to act as a TSH-releasing factor (TRF) in chickens, amphibians, and teleosts (16, 21, 26 -30), in addition to its classic action on pituitary ACTH secretion (9,16,29,(31)(32)(33)(34)(35). In view of the fact that TRH and CRH can stimulate the secretion of multiple pituitary hormones in chickens and other lower vertebrates, it raises an intriguing, but fundamental, question, whether a hypothalamic releasing factor specific for TSH secretion exists and functions in nonmammalian vertebrates, such as in chickens.…”
mentioning
confidence: 99%
“…For the ontogeny experiment, samples were taken from embryos on d 16,18, and 20 of the incubation (E16, E18, and E20) and from 1-d-old chicks (C1). Blood was collected after heart puncture/decapitation and centrifuged at 1800 ϫ g at 4 C for 15 min.…”
mentioning
confidence: 99%